(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The paper studies democratic style of leadership and how the style influences the practices of leadership. Leadership can be categorized based on the level of involving team members and participating in the decision making process. The study is exploratory in nature and attempts to explore and analyze the democratic aspects of leadership style and its influence in the practices of leadership. The study adopts survey and interview techniques and 25 leaders of the state Manipur, India are considered as sample. The primary data are collected using interview cum questionnaire method from the top executives of the selected 25 organizations and also from two immediate subordinates of the sampled executives of the selected organizations and from two immediate subordinates of the sampled executives. The responses of the followers become essential to crosscheck the practices of the leaders. The study highlights how the democratic style influences the practice of leadership.